2014
DOI: 10.1111/hepr.12400
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of the anticoagulant drug, danaparoid sodium, in the treatment of portal vein thrombosis in patients with liver cirrhosis

Abstract: Danaparoid sodium for the treatment of PVT in patients with liver cirrhosis was safe and effective. Therefore, anticoagulation therapy with danaparoid sodium could have potential as one of the treatment options in PVT accompanied by cirrhosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 33 publications
(41 reference statements)
4
39
0
Order By: Relevance
“…The main findings were that 2 weeks of treatment with danaparoid sodium reduced PVT in all patients. These results are similar to those reported previously, 12 confirming that danaparoid sodium is safe and effective for the treatment of PVT in patients with liver cirrhosis. Subsequent treatment with edoxaban significantly reduced the volume of PVT and this effect was observed at 1, 3, and 6 months, with a CR rate at 6 months of 70%.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The main findings were that 2 weeks of treatment with danaparoid sodium reduced PVT in all patients. These results are similar to those reported previously, 12 confirming that danaparoid sodium is safe and effective for the treatment of PVT in patients with liver cirrhosis. Subsequent treatment with edoxaban significantly reduced the volume of PVT and this effect was observed at 1, 3, and 6 months, with a CR rate at 6 months of 70%.…”
supporting
confidence: 92%
“…11 Unfortunately, warfarin is limited by a narrow therapeutic window and a highly variable dose-response requiring frequent dose adjustments and monitoring. Recently, Naeshiro et al 12 reported the efficacy and safety of anticoagulation therapy with danaparoid sodium in cirrhotic patients with PVT. Danaparoid sodium used for the treatment of pulmonary embolism and deep vein thrombosis in the cardiovascular field is a heparinoid glycosaminoglycuronan antithrombotic agent.…”
Section: Introductionmentioning
confidence: 99%
“…It is a glycosaminoglycan mixture containing 84% heparin sulfate, dermatan sulfate, and chondroitin sulfate resulting in 10% incidence of HIT. [2021] It has a long elimination half-life of 22 h that could be prolonged with renal insufficiency. There is no antidote, coagulation monitoring can be done by measuring anti-Xa activity.…”
Section: Factor Xa Inhibitorsmentioning
confidence: 99%
“…Sixteen of 960 initially identified papers, both abstracts and full papers, reporting data on 430 patients were included [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Overall, the rate of AC-related bleeding ranged from 0 to 18%.…”
Section: Treatment Of Pvt In Cirrhosismentioning
confidence: 99%
“…However, further randomizedcontrolled trials are warranted to confirm the risk-tobenefit ratio of anticoagulation in such patients, especially AC-related bleeding [37]. To the best of the author's knowledge, there are no data supporting whether any one regimen of anticoagulation is better than another [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. Moreover, recent data have reported both the efficacy and the safety of new oral ACs as a treatment of PVT [56][57][58].…”
Section: Treatment Of Pvt In Cirrhosismentioning
confidence: 99%